1999
DOI: 10.4315/0362-028x-62.8.872
|View full text |Cite
|
Sign up to set email alerts
|

Toxin Production by Clostridium botulinum in Pasteurized Milk Treated with Carbon Dioxide

Abstract: The addition of carbon dioxide to milk at levels of <20 mM inhibits the growth of selected spoilage organisms and extends refrigerated shelf life. Our objective was to determine if the addition of CO2 influenced the risk of botulism from milk. Carbon dioxide was added to pasteurized 2% fat milk at approximately 0, 9.1, or 18.2 mM using a commercial gas-injection system. The milk was inoculated with a 10-strain mixture of proteolytic and nonproteolytic Clostridium botulinum spore strains to yield 10(1) to 10(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Werner and Hotchkiss (2002) advocated that the addition of moderate levels of CO 2 (11.9 mM) did not have either stimulatory or inhibitory effect on the initiation of germination and subsequent outgrowth of B. cereus spores over long‐term storage and did not increase the risk of food borne illness. Similar conclusions were made regarding C. botulinum (Glass et al. 1999).…”
Section: Preservation Of Dairy Products By Co2 Additionsupporting
confidence: 81%
“…Werner and Hotchkiss (2002) advocated that the addition of moderate levels of CO 2 (11.9 mM) did not have either stimulatory or inhibitory effect on the initiation of germination and subsequent outgrowth of B. cereus spores over long‐term storage and did not increase the risk of food borne illness. Similar conclusions were made regarding C. botulinum (Glass et al. 1999).…”
Section: Preservation Of Dairy Products By Co2 Additionsupporting
confidence: 81%
“…We have investigated the effect of added CO 2 on B. cereus and C. botulinum growth and toxigenesis in milk (Glass and others 1999; Werner and Hotchkiss 2002). While CO 2 at levels of <20 mM inhibits the growth of selected spoilage organisms and extends refrigerated shelf life, CO 2 could influence the risk of botulism from milk.…”
Section: Co2 Processing and Packaging Technologymentioning
confidence: 99%
“…While CO 2 at levels of <20 mM inhibits the growth of selected spoilage organisms and extends refrigerated shelf life, CO 2 could influence the risk of botulism from milk. In the latter study (Glass and others 1999), pasteurized 2% fat milk was modified with approximately 0, 9.1, or 18.2 mM CO 2 and inoculated with a 10‐strain mixture of proteolytic and nonproteolytic C. botulinum spore strains to yield 10 1 to 10 2 spores mL ‐1 . The milk was stored at 6.1 °C for 60 d or 21 °C for 6 d in sealed glass jars or high‐density polyethylene (HDPE) plastic bottles.…”
Section: Co2 Processing and Packaging Technologymentioning
confidence: 99%
“…Studies to date on the effect of CO 2 on the growth of Listeria monocytogenes, Bacillus cereus and Clostridium sporogenes in milk or cottage cheese and toxingenesis of Clostridium botulinum in milk have shown that CO 2 treatment does not pose increased risk with regard to these factors (Chen and Hotchkiss, 1993;Glass et al, 1999;Werner and Hotchkiss, 2002). In addition, culture-independent studies on the native bacterial composition of carbonated raw milk during cold storage have found no evidence of selection of harmful bacteria (Rasolofo et al, 2011;Rasolofo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%